Origin of an Alternative Genetic Code in the Extremely Small and GC–Rich Genome of a Bacterial Symbiont - McCutcheon, John P.; McDonald, Bradon R.; Moran, Nancy A. (PLOS Genetics, 2009)
Author Summary The genetic code, which relates DNA sequence to protein sequence, is nearly universal across all life. Examples of recodings do exist, but new instances are rare. Genomes that exhibit recodings typically have other extreme properties, including reduced size, reduced gene sets, and low guanine plus cytosine (GC) content. The most common recoding event, the reassignment of UGA to Tryptophan instead of Stop (Stop→Trp), was previously known from several mitochondrial and one bacterial lineage, and it was proposed to be driven by extinction of the UGA codon due to reduction in GC content. Here we present an unusual bacterial genome from a symbiont of cicadas. It exhibits the UGA Stop→Trp reassignment, but has a high GC content, showing that reduction in GC content is not a necessary condition for this recoding. This symbiont genome is also the smallest known for any cellular organism. We therefore propose gene loss during genome reduction as the common force driving this code change in bacteria and organelles. Additionally, the extremely small size of the genome further obscures the once-clear distinction between organelle and autonomous bacterial life.